Life during furlough: Challenges to dignity from a changed employment status. Issue 6 (24th October 2022) - Hamilton, Peter; Harness, Oonagh; Griffin, Martyn
Abstract: In response to the COVID‐19 virus, the UK government introduced the Job Retention Scheme in March 2020. The scheme, a novelty in the United Kingdom, provided income support to those furloughed from work. In this paper, we examine how individuals in several occupations and organisations experienced furlough and how they were treated during this enforced period of work absence. Beyond describing their experiences during the furlough, we examine how these experiences threatened and challenged their sense of dignity. Experientially we report on furlough as a time that elicited both delight and despair. The analysis of dignity relates to how treatment based on their employment status rendered many employees marginalised and cast adrift.